Comparison of the surgical outcomes between paravaginal repair and anterior colporrhaphy: A retrospective case–control study - Pei-Chen Chen; Wing Lam Tsui; Dah-Ching Ding (Tzu Chi Medical Journal)
OBJECTIVES: This study compared the surgical outcomes of anterior vaginal wall repair (A-repair) and paravaginal repair (PVR) for laparoscopic pelvic organ prolapse (POP) surgeries. MATERIALS AND METHODS: This retrospective case–control study recruited patients who underwent laparoscopic POP surgeries in our hospital from May 1, 2013, to May 31, 2022, using the health insurance surgical code payment system (laparoscopic colpopexy/hysteropexy/cervicopexy: 80025B) in Taiwan. The patients were divided into A-repair (group 1) and PVR (group 2). Patients aged <20 years, without postoperative outcomes, and without baseline characteristics were excluded. Baseline characteristics (age, menopausal status, parity, diabetes mellitus, and hypertension) were collected. The outcome was to compare the changes in Pelvic Organ Prolapse Quantification (POP-Q) scores (Aa, Ba, and total vaginal length) preoperatively and 1–2 months, 3–6 months, and 1 year postoperatively in the two groups. Results: After exclusion, 23 and 10 patients in A-repair and PVR, respectively, were recruited. There was no significant difference in baseline characteristics between the two groups. Patients in both groups showed significant improvement in Aa and Ba of POP-Q 1–2 months and 3–6 months postoperatively, except for those in group 2 1 year postoperatively. However, there was no significant difference in postoperative scores between the two groups at 1–2 months, 3–6 months, and 1 year postoperatively. The estimated blood loss did not exhibit a significant difference between the two groups; however, PVR had a longer duration of operation. Conclusion: The surgical outcomes of A-repair and PVR for the anterior compartment were comparable at 1–2 months, 3–6 months, and 1 year postoperatively.